The impact of supply chain management practices on organizational performance / Mohd Hafiz Mohd Muhili - Mohd Muhili, Mohd Hafiz (Faculty of Business Management, 2017)
Achieving some standard of performance is the objective of all organizations because through these performances, organizations are able to grow and progress. Over the past twenty years, the field of supply chain management has progressed to become the backbone of today’s businesses. It is arguably accepted that competition is no longer between organizations rather, between supply chains. Supply chain management is very complex and is one of the major determinant of success or failure in any company. Effective supply chain management has become one of the most prized way to achieve organizational performance. The purpose of this research is to investigate the impact of supply chain management practices on organizational performance and to determine the direction of the effect as well as the most influential supply chain management practices towards the organizational performance across various industries in Malaysia. This research is a quantitative research which had used the self-administered electronic questionnaire as the instrument for the collection of data. The data was collected and viable at a percentage of 51% out of the possible 226 respondents which was derived from the total population of 440 elements. Sample selection was based on simple random sampling method. The data collected was then evaluated by using Statistical Package for the Social Science (SPSS) Version 20 Software. Using SPSS, numerous tests were converged such as reliability analysis, frequency distribution, descriptive analysis, Pearson’s correlation analysis and multiple regression. The results indicated that supply chain management practices which include supplier partnership, customer relationship, and information sharing and information quality are related to organizational performance.